Cultural minorities in Finland : an overview towards cultural policy - Hiltunen, Marja; Pentikäinen, Juha; Wynne-Ellis, Michael; Finnish National Commission for Unesco (Publications of the Finnish National Commission for Unesco, ISSN 0357-1106, 1995)
Suomen Unesco-toimikunta.Writers: Juha Pentikäinen, Veikko Anttonen; Lassi Saressalo; Marja Nylund-Oja, Karmela Liebkind, Roger Broo, Fjalar Finnäs, Katja Hyry, Irja Seurujärvi-Kari, Matti Morottaja, Vuokko Hirvonen, Ulla Aikio-Puoskari, Martti Grönfors, Frank Horn, Magdalena Jaakkola, Laura Yli-Vakkuri. Sisältää mm.: uususkonnot; kristityt; ortodoksit; muslimit; Suomen tataarit.
Keywords: Minorities : Finland; Finland : ethnology; emigration and immigration; minority groups : Finland; etniset ryhmät; kansalliset vähemmistöt; karjalaiset; kielelliset vähemmistöt; kulttuuri; pakolaiset; romanit; saamelaiset; siirtolaiset; suomenruotsalaiset; venäläiset; etninen identiteetti; inkeriläiset; juutalaiset; kieli ja kielet; kulttuurihistoria; kulttuurintutkimus; vähemmistöt; kulttuuripolitiikka; lait; maahanmuuttajat; maassamuutto; maastamuutto; monikulttuurisuus; siirtolaispolitiikka; tataarit; ulkomaalaiset; uskonnolliset vähemmistöt; väestö; etniset vähemmistöt; ihmisoikeudet; etniska grupper; nationella minoriteter; karelare; språkliga minoriteter; kultur; flyktingar; romer; samer; migranter; finlandssvenskar; ryssar; etnisk identitet; ingermanlänningar; judar; språk; kulturhistoria; kulturforskning; minoriteter; kulturpolitik; lagar; invandrare; intern migration; utvandring; mångkulturalism; migrationspolitik; tatarer; utlänningar; religiösa minoriteter; befolkning; etniska minoriteter; mänskliga rättigheter; Suomi; Finland; Minoriteter : etniska : Finland; Northern cultures and societies; Suomen venäläiset; cultural policy : Finland; ethnic groups : Finland; etniset kysymykset; minoriteter : kulturella : Finland; minorities : Finland; ulkomaalainen; religiösaminoriteter